2019
DOI: 10.1111/obr.12940
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bariatric surgery on serum uric acid levels and the incidence of gout—A meta‐analysis

Abstract: Gout is characterized by high serum uric acid (SUA) levels and arthritis. It is associated with obesity and metabolic syndrome. Bariatric surgery has been associated with decreased SUA levels and overall gout incidence. This meta-analysis aims to summarize the current evidence on bariatric surgery, gout and SUA levels. A literature review was performed on papers published from 2000 up till December 2018.Original studies investigating the impact of bariatric surgery on SUA levels or gout incidence were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 59 publications
2
27
0
3
Order By: Relevance
“…33,34 However, weight reduction was shown to be associated with a significant decrease in UA levels. 11,12 In this study, we confirmed the possible interdependent relationship between UGE and LAP in predicting hyperuricemia.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…33,34 However, weight reduction was shown to be associated with a significant decrease in UA levels. 11,12 In this study, we confirmed the possible interdependent relationship between UGE and LAP in predicting hyperuricemia.…”
Section: Discussionsupporting
confidence: 80%
“…Of these risk factors, obesity has a clear effect on UA levels. 11,12 However, in recent years, the distribution of fat accumulation in the body, rather than overweight or obesity per se, is becoming increasingly important for a variety of physiological aberrations. [13][14][15] Many studies did not consider the impact of fat distribution on UA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These controversial results might find their explanation in timing and weight loss amplitude, as food groups that typically increase serum uric acid levels are widely consumed in ketogenic diets and might lead to such an effect in the short term [24]. However, it is acknowledged that weight loss is associated with a significant reduction in urate levels [25]. As our patients experienced a mean weight loss of nearly 20% of baseline values, it seems reasonable to conclude that this aspect might have played a predominant role in modulating uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery is currently an effective treatment modality for obesity and associated metabolic syndrome [1,2]. However, in this unprecedented global crisis, it is important that nonurgent clinic appointments and operations be postponed in order to conserve resources and reduce risks of viral transmission [3].…”
Section: Introductionmentioning
confidence: 99%